Ratiometric Photoacoustic Molecular Imaging for Methylmercury Detection in Living Subjects - Liu, Yi (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.